Impact assessment of cotton research in Zimbabwe: 1970-1995 - Mudhara, M.; Anandajayasekeram, P.; Kupfuma, B.; Mazhangara, E.P. (CAB International, 2007)
This study analyses the impact of cotton research and Development in Zimbabwe from 1970 to 1995. A benefit-cost analysis calculated a 47% rate of return to cotton R&D investments and showed that the investments in past cotton R&D were profitable. The assessment of the institutional impact showed that the success of the cotton industry was a result of, carefully designed research, extension, marketing, credit and farmer training programmes. Overall, the study showed that integrated commodity-based research and Development can generate positive dividends to public sector investment.